PENDEKATAN METODE FAULT TREE ANALYSIS DALAM KESEHATAN DAN KESELAMATAN KERJA SERTA PENGARUHNYA TERHADAP PRODUKTIFITAS - Firman Ardiansyah Ekoanindiyo; Antoni Yohanes Yohanes; Endro Prihastono Prihastono; Enty Nur Hayati Hayati (Universitas Putera Batam, 2021)
CV ABC is one of the manufacturing industries in Central Java that produces furniture products. The resulting products have good quality so that 60-70 percent of their products are exported while the rest are marketed domestically. The current production process, the application of occupational safety and health have not been fully implemented. From company data for three years, the number of work accidents is 9, 8, and 10 times. The number of hours lost was 154 hours, 168 hours, and 224 hours. Efforts are needed to prevent work accidents that can reduce work productivity. Based on the existing problems, the company needs to identify the causes of work accidents with a fault tree analysis method approach. The factors that cause work accidents can be identified, namely the work area, production process and storage and transfer. This work accident will cause worker productivity to decrease. In 2016 the productivity value was 0.99925, in 2017 the productivity level was 0.99929. In 2017 there was an increase in productivity due to the reduced number of lost hours. In 2018 there was a decrease in the productivity level to 0.99910 due to the increase in the number of lost hours of employees becoming more. The results of the